The Implementation of Banking Risk Management in Southeast Asian Countries - Julia Safitri; Ira Geraldina (Faculty of Economics and Business Universitas Jenderal Soedirman, 2023)
The purpose of this study is to empirically examine the impact of credit risk, liquidity risk and interest rate on the performance of banks through capital adequacy. Banking companies in five Southeast Asian countries were used as data source in this quantitative research. The total sample obtained was 175 from 2014 to 2020. This Predictive and exploratory inquiry used Partial Least Squares (PLS) Structural Equation Modelling (SEM) with WarpPLS 7.0 application. The study found that credit risk significantly affected bank performance. The VAF calculation to see whether the capital adequacy as a mediator can be categorised as partial mediation or not also showed a similar finding. A mediation test was carried out using the VAF method where the conditions were 20% < VAF < 80%. From the results of data analysis, capital adequacy showed to be able to mediate the indirect impact of credit risk on bank performance. The result, therefore, validated the Commercial Loan hypothesis, which states that if a bank's productive assets, which consist of short-term loans, are distributed in normal business activities, bank liquidity will be ensured. This study indicated that credit risk in Southeast Asian Countries requires sufficient capital reserves to reduce the occurrence of credit risk which will have an impact on decreasing bank performance.